2016
DOI: 10.1515/pjvs-2016-0042
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and immunoreactivity of canine and feline extramedullary plasmacytomas

Abstract: The aim of the study was the evaluation of morphology and immunophenotype of canine (19 cases) and feline (7 cases) extramedullary plasmacytomas. Tumours, located in skin, oral cavity and spleen were surgically excised, fixed and processed for histopathology and immunohistochemistry (CD79α, CD18, proliferating cell nuclear antigen, metallothionein). Histologically, tumours were classified into mature, cleaved, asynchronous, polymorphous blastic, hyalin, or monomorphous blastic type. All evaluated tumours showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…They typically present as small, slightly raised dermal nodules, with skin showing loss of hair and occasionally ulceration [ 6 ]. As in humans, canine and feline EMPs have been subclassified based on histological features, including asynchronous, cleaved, hyaline, mature, and polymorphous subtypes [ 3 , 4 , 12 , 13 ]; however, they have not been associated with any prognostic significance [ 3 ]. The presence of amyloid can be a helpful diagnostic feature for plasmacytomas, and, although not observed in this case, it has been reported in ~10% of canine plasmacytomas [ 6 ] and one study of feline plasmacytomas found its presence in 3/9 (33%) cases [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They typically present as small, slightly raised dermal nodules, with skin showing loss of hair and occasionally ulceration [ 6 ]. As in humans, canine and feline EMPs have been subclassified based on histological features, including asynchronous, cleaved, hyaline, mature, and polymorphous subtypes [ 3 , 4 , 12 , 13 ]; however, they have not been associated with any prognostic significance [ 3 ]. The presence of amyloid can be a helpful diagnostic feature for plasmacytomas, and, although not observed in this case, it has been reported in ~10% of canine plasmacytomas [ 6 ] and one study of feline plasmacytomas found its presence in 3/9 (33%) cases [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study found the most frequent site of origin to be the skin [ 5 ], whilst other reports suggested oral plasmacytomas are the most common [ 1 , 2 , 3 ]. The incidence of plasmacytomas in cats is much lower, and the literature mostly consists of case reports of a single animal [ 7 , 8 , 9 , 10 , 11 ], although there are some studies with larger sample numbers ( n = 7–11) [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of the reported cases of feline NCEMP, the cats were usually of an older age and mainly American Shorthair and European Shorthair, as in this case. [4][5][6][7][8][9][10][11][12][13][14] Other differential diagnoses were lymphoplasmacytic lymphoma (LPL) and MM. Previously, a case of feline cutaneous LPL with systemic metastasis has been reported in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Myeloma-related disorders (MRDs) are infrequent diseases in cats, 14 and are classified as multiple myeloma (MM), cutaneous extramedullary plasmacytoma (CEMP), non-CEMP (NCEMP), solitary plasmacytoma of the bone, IgM macroglobulinaemia (Waldenström macroglobulinaemia), immunoglobulin-secreting lymphoma and myeloma cell leukaemia. 2,3 Feline NCEMP is generally reported to originate from the spleen, 2,5 liver, 2 intracerebral tissue, 6 intraocular tissue, 7 orbital tissue, 2,8 respiratory tract, 911 subcutaneous tissue, 4 oral cavity, 5,12 mesentery tissue 13 or stomach. 14 There are few cases reporting pathological involvement of the intestine in feline MRD.…”
Section: Introductionmentioning
confidence: 99%